(untitled) (Research, Society and Development, 2021)
Objective: To analyze the preventable fraction of physical activity and cancer. Methodology: This is a narrative review of literature in the databases, using articles from the last 10 years and articles in Portuguese, English and Spanish. Results: The incidence of cancer, as well as other chronic diseases, has increased in recent years as a result of the modern lifestyle characterized by an unregulated diet, sedentary lifestyle and exposure to chemical, physical and biological agents. Physical activity, in recent decades, is no longer part of man’s routine. It is known that the practice is related to the strengthening of the immune response, which is extremely important to combat neoplastic cells. The results found were cancer as a public health problem, physical activity, evidence of the association between physical activity and cancer, relationship between cancer and physical activity, mechanisms, exercise and immune system, immunological parameters of exercise and infection, and preventable fraction. Final Considerations: Prevention strategies are significantly modifying the lifestyle, so that they enable the performance of physical activities on a regular basis and that help to control body weight and consequently a better quality of life.